Fetal overgrowth in the Cdkn1c mouse model of Beckwith-Wiedemann syndrome - Simon J. Tunster; Mathew Van de Pette; Rosalind M. John (The Company of Biologists, 2011)
SUMMARY Mutations in the imprinted CDKN1C gene are associated with the childhood developmental disorder Beckwith-Wiedemann syndrome (BWS). Multiple mouse models with deficiency of Cdkn1c recapitulate some aspects of BWS but do not exhibit overgrowth of the newborn, a cardinal feature of patients with BWS. In this study, we found that Cdkn1c mutants attained a 20% increase in weight during gestation but experienced a rapid reversal of this positive growth trajectory very late in gestation. We observed a marked effect on placental development concurrently with this loss of growth potential, with the appearance of large thrombotic lesions in the labyrinth zone. The trilaminar trophoblast layer that separates the maternal blood sinusoids from fetal capillaries was disordered with a loss of sinusoidal giant cells, suggesting a role for Cdkn1c in maintaining the integrity of the maternal-fetal interface. Furthermore, the overgrowth of mutant pups decreased in the face of increasing intrauterine competition, identifying a role for Cdkn1c in the allocation of the maternal resources via the placenta. This work explains one difficulty in precisely replicating BWS in this animal model: the differences in reproductive strategies between the multiparous mouse, in which intrauterine competition is high, and humans, in which singleton pregnancies are more common.